High-strength ceramic fiber gasket and production method thereof

By using composite reinforcing materials and optimized processes, the tensile strength and tear resistance of ceramic fiber gaskets are improved, solving the problem of easy damage of existing ceramic fiber gaskets under harsh working conditions, and achieving comprehensive performance improvements in high strength, high thermal insulation and corrosion resistance.

CN120682042APending Publication Date: 2025-09-23JIANGSU JIENAITE NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510597419.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing ceramic fiber gaskets are easily damaged and torn under harsh working conditions such as high temperature, high pressure, and strong vibration, resulting in a decrease in sealing performance. Existing reinforcement measures such as adding metal wire will cause stress concentration and reduced flexibility, and cannot simultaneously meet multiple stringent requirements such as high strength, high thermal insulation, and high stability.

Method used

By using high-strength organic fibers, nano-reinforced particles, graphene aerogels, carbon nanotubes, boron nitride nanosheets and basalt fibers and optimizing the raw material formula and production process, a composite reinforcement system is formed to improve tensile strength and tear resistance while maintaining good thermal insulation, high temperature resistance and corrosion resistance.

Benefits of technology

The tensile strength and tear resistance of ceramic fiber gaskets are significantly improved, enabling long-term stable use in high-temperature environments, maintaining excellent thermal insulation and corrosion resistance, improving thermal conductivity uniformity and electromagnetic shielding performance, and adapting to complex working conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-strength ceramic fiber gasket and a production method thereof. The gasket is prepared from the following raw materials in parts by weight: 60-80 parts of ceramic fibers, 10-20 parts of high-strength organic fibers, 5-15 parts of nano reinforced particles, 5-10 parts of a high-temperature binder, 2-5 parts of graphene aerogel, 1-3 parts of carbon nanotubes, 1-3 parts of boron nitride nanosheets and 5-10 parts of basalt fibers. According to the high-strength ceramic fiber gasket and the production method thereof, various reinforcing materials such as the high-strength organic fibers, the nano reinforced particles, the graphene aerogel, the carbon nanotubes, the boron nitride nanosheets and the basalt fibers are added to form a composite reinforcing system, and the tensile strength and the tear resistance of the gasket are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sealing gaskets, in particular to a high-strength ceramic fiber gasket and a production method thereof. Background Art

[0002] In modern industry, ceramic fiber gaskets, thanks to their excellent thermal insulation, high-temperature resistance, and corrosion resistance, are widely used for thermal insulation, heat insulation, and dust-proof sealing of high-temperature equipment in industries such as metallurgy, chemicals, and power generation. For example, ceramic fiber gaskets play a key role in sealing metallurgical blast furnaces, insulating chemical reactors, and maintaining the heat of power boilers, effectively ensuring stable equipment operation and reducing heat loss and media leakage.

[0003] Traditional ceramic fiber gaskets face numerous challenges in practical applications. Their inherent strength is low, particularly in tensile strength and tear resistance. Under harsh operating conditions such as high temperature, high pressure, and strong vibration, gaskets are prone to breakage and tearing, leading to a rapid decline in sealing performance or even failure. This can lead to dust and media leaks, impacting production efficiency and potentially causing serious safety hazards and environmental pollution.

[0004] To enhance the strength of ceramic fiber gaskets, existing technologies employ improvements such as incorporating reinforcing materials like metal filaments. However, the significant difference in thermal expansion coefficients between metal filaments and ceramic fibers can lead to stress concentration in high-temperature environments, damaging the gasket's internal structure. Furthermore, the addition of metal filaments weakens the gasket's flexibility, making it difficult to adapt to complex sealing environments, and reduces its corrosion resistance, shortening its service life. Furthermore, ceramic fiber gaskets currently on the market have made limited progress in improving their overall performance, failing to simultaneously meet the stringent requirements of high strength, high thermal insulation, and high stability.

[0005] Therefore, the development of a ceramic fiber gasket and its production method that can significantly enhance strength while maintaining excellent thermal insulation, high temperature resistance, corrosion resistance and other properties, and is suitable for a variety of complex working conditions, has become a key issue that needs to be urgently solved in this field. It has important practical significance and broad market prospects. Summary of the Invention

[0006] (1) Technical problems solved

[0007] In response to the shortcomings of the existing technology, the present invention provides a high-strength ceramic fiber gasket and a production method thereof. By optimizing the raw material formula and production process, the tensile strength, tear resistance and comprehensive performance of the ceramic fiber gasket are effectively improved, solving the problems of low strength and easy breakage of the existing ceramic fiber gasket, so that it can be used stably and reliably under harsh working conditions such as high temperature, high pressure, and strong corrosion.

[0008] (2) Technical solution

[0009] To achieve the above object, the present invention provides the following technical solution: a high-strength ceramic fiber gasket, which is made of the following raw materials in parts by weight:

[0010] 60-80 parts of ceramic fiber, 10-20 parts of high-strength organic fiber, 5-15 parts of nano-reinforced particles, 5-10 parts of high-temperature adhesive, 2-5 parts of graphene aerogel, 1-3 parts of carbon nanotubes, 1-3 parts of boron nitride nanosheets, and 5-10 parts of basalt fiber.

[0011] Preferably, the ceramic fiber is a mixture of one or more of aluminum silicate fiber, mullite fiber, and alumina fiber, and has a diameter of 1-5 μm and a length of 10-50 mm.

[0012] Preferably, the high-strength organic fiber is one of aramid fiber and ultra-high molecular weight polyethylene fiber, or a mixture of the two, and has a diameter of 5-15 μm and a length of 5-20 mm.

[0013] Preferably, the nano-reinforced particles are a mixture of one or more of nano-silicon dioxide, nano-aluminum oxide, and nano-zirconium oxide, and the particle size thereof is 50-200 nm.

[0014] Preferably, the high-temperature binder is a mixture of one or more of silica sol, aluminum phosphate solution, and water glass.

[0015] Preferably, the particle size of the graphene aerogel after crushing is 1-5 mm, and the carbon nanotubes are dispersed in an ultrasonic disperser at a power of 300-500 W for 20-30 minutes before use.

[0016] Preferably, the boron nitride nanosheets have a diameter of 0.5-2 μm and a thickness of 5-20 nm, and the basalt fibers have a diameter of 7-15 μm and a length of 15-30 mm.

[0017] A method for preparing a high-strength ceramic fiber gasket comprises the following steps:

[0018] S1: Raw material pretreatment: calcining ceramic fiber in a high-temperature furnace at 500-600°C for 2-3 hours; soaking high-strength organic fiber in an organic solvent for 1-2 hours, and then drying at 80-100°C; stirring nano-reinforced particles in a high-speed blender at a speed of 1000-1500 r / min for 30-60 minutes; crushing graphene aerogel to a particle size of 1-5 mm; dispersing carbon nanotubes in an ultrasonic disperser at a power of 300-500W for 20-30 minutes; ultrasonically dispersing boron nitride nanosheets in deionized water at an ultrasonic power of 200-400W for 15-25 minutes; soaking basalt fiber in a coupling agent solution for 0.5-1 hour, and then drying at 60-80°C;

[0019] S2: Mixing ingredients: Add the pretreated ceramic fibers, high-strength organic fibers, nano-reinforced particles, graphene aerogel, carbon nanotubes, boron nitride nanosheets, and basalt fibers to a high-speed mixer according to the weight ratio, and mix at a speed of 800-1200 r / min for 30-40 minutes. During the mixing process, gradually add the high-temperature binder and continue stirring for 10-20 minutes to form a uniform mixture.

[0020] S3: Molding: Place the mixed material into a mold and perform cold pressing on a press at a pressure of 10-20 MPa to form a gasket blank. Place the gasket blank in a drying oven and dry it at 100-120°C for 2-3 hours.

[0021] S4: High temperature sintering: Place the dried gasket blank into a high temperature furnace, heat it to 1200-1400°C at a heating rate of 5-10°C / min, keep it at that temperature for 2-3 hours, and cool it to room temperature along with the furnace.

[0022] Preferably, in the S1 raw material pretreatment, the organic solvent used for soaking the high-strength organic fiber is acetone or ethanol, and the coupling agent solution is a silane coupling agent solution with a mass fraction of 1-3%.

[0023] Preferably, in the step S2 of mixing ingredients, the high-temperature binder is a mixed binder of silica sol and aluminum phosphate solution, and the mass ratio of the two is 2:1.

[0024] (3) Beneficial effects

[0025] Compared with the prior art, the present invention provides a high-strength ceramic fiber gasket and a production method thereof, which has the following beneficial effects:

[0026] 1. This high-strength ceramic fiber gasket and its production method form a composite reinforcement system by adding multiple reinforcing materials, such as high-strength organic fibers, nano-reinforcement particles, graphene aerogel, carbon nanotubes, boron nitride nanosheets and basalt fibers, which significantly improves the tensile strength and tear resistance of the gasket.

[0027] 2. This high-strength ceramic fiber gasket and its production method, while improving strength, maintains excellent thermal insulation, high-temperature resistance, and corrosion resistance thanks to the selection of appropriate raw materials and production processes. Its thermal insulation performance is comparable to that of traditional ceramic fiber gaskets, allowing for long-term use in high-temperature environments of 1000-1200°C and excellent resistance to corrosive media such as acids and alkalis. Furthermore, the incorporation of graphene aerogel and carbon nanotubes imparts improved thermal conductivity and electromagnetic shielding properties to the gasket; the addition of boron nitride nanosheets enhances the gasket's lubricity and high-temperature resistance; and the addition of basalt fiber strengthens its fatigue resistance. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0029] Example 1:

[0030] Raw materials preparation:

[0031] Ceramic fiber: aluminum silicate fiber, diameter 3 μm, length 30 mm, 70 parts.

[0032] High-strength organic fiber: aramid fiber, diameter 10μm, length 15mm, 15 parts.

[0033] Nano-reinforced particles: nano-silicon dioxide, particle size 100nm, 10 parts.

[0034] High temperature binder: silica sol, 5 parts.

[0035] Graphene aerogel: 3 parts, with a particle size of 3 mm after crushing.

[0036] Carbon nanotubes: 2 parts, dispersed in an ultrasonic disperser at 400 W power for 25 minutes.

[0037] Boron nitride nanosheets: 1 part, sheet diameter 1 μm, thickness 10 nm.

[0038] Basalt fiber: 5 parts, diameter 10 μm, length 20 mm.

[0039] Production steps:

[0040] S1: Raw material pretreatment: calcining aluminum silicate fiber in a high-temperature furnace at 550°C for 2.5 hours; soaking aramid fiber in acetone for 1.5 hours and then drying at 90°C; stirring nano-silica in a high-speed blender at a speed of 1200r / min for 45 minutes; crushing graphene aerogel; ultrasonically dispersing carbon nanotubes; ultrasonically dispersing boron nitride nanosheets in deionized water at a power of 300W for 20 minutes; soaking basalt fiber in a 2% by mass silane coupling agent solution for 0.8 hour and then drying at 70°C.

[0041] S2: Mixing ingredients: Add the pretreated raw materials into a high-speed mixer and mix at a speed of 1000 r / min for 35 minutes. During the mixing process, gradually add silica sol and continue stirring for 15 minutes.

[0042] S3: Molding: The mixed material is placed in a mold and cold-pressed on a press at a pressure of 15 MPa to form a gasket blank, which is then placed in a drying oven and dried at 110° C. for 2.5 hours.

[0043] S4: High temperature sintering: Place the dried gasket green body into a high temperature furnace, heat it to 1300°C at a heating rate of 8°C / min, keep it at that temperature for 2.5 hours, and cool it to room temperature along with the furnace.

[0044] Performance test: After testing, the gasket has a tensile strength of 18MPa and a tear resistance of 12N / mm. After 1000 hours of continuous use in a high temperature environment of 1100°C, there is no significant performance degradation. It has good thermal insulation performance, a 20% increase in thermal conductivity uniformity, an electromagnetic shielding effectiveness of 10dB, and good resistance to corrosive media such as acids and alkalis.

[0045] Example 2:

[0046] Raw materials preparation:

[0047] Ceramic fiber: a mixed fiber of mullite fiber and alumina fiber (mass ratio 1:1), diameter 4 μm, length 40 mm, 65 parts.

[0048] High-strength organic fiber: ultra-high molecular weight polyethylene fiber, diameter 12μm, length 18mm, 18 parts.

[0049] Nano-reinforced particles: mixed particles of nano-alumina and nano-zirconia (mass ratio 1:1), particle size 150nm, 12 parts.

[0050] High-temperature adhesive: 5 parts of a mixed adhesive of aluminum phosphate solution and water glass (mass ratio 1:1).

[0051] Graphene aerogel: 4 parts, with a particle size of 2 mm after crushing.

[0052] Carbon nanotubes: 2.5 parts, dispersed in an ultrasonic disperser at a power of 450 W for 28 minutes.

[0053] Boron nitride nanosheets: 2 parts, sheet diameter 1.5 μm, thickness 15 nm.

[0054] Basalt fiber: 8 parts, diameter 12 μm, length 25 mm.

[0055] Production steps:

[0056] S1: Raw material pretreatment: calcining the mixed ceramic fiber in a high-temperature furnace at 580°C for 2.8 hours; soaking the ultra-high molecular weight polyethylene fiber in ethanol for 1.8 hours and then drying it at 95°C; stirring the mixed nano-reinforced particles in a high-speed stirrer at a speed of 1300r / min for 50 minutes; crushing the graphene aerogel; ultrasonically dispersing the carbon nanotubes; ultrasonically dispersing the boron nitride nanosheets in deionized water at a power of 350W for 22 minutes; soaking the basalt fiber in a 2% by mass silane coupling agent solution for 0.9 hour and then drying it at 75°C.

[0057] S2: Mixing ingredients: Add the pretreated raw materials into a high-speed mixer and mix at a speed of 1100 r / min for 38 minutes. During the mixing process, gradually add the mixed high-temperature binder and continue stirring for 18 minutes.

[0058] S3: Molding: The mixed material is placed in a mold and cold-pressed on a press at a pressure of 18 MPa to form a gasket blank, which is then placed in a drying oven and dried at 115° C. for 2.8 hours.

[0059] S4: High temperature sintering: Place the dried gasket green body into a high temperature furnace, heat it to 1350°C at a heating rate of 9°C / min, keep it at that temperature for 2.8 hours, and cool it to room temperature along with the furnace.

[0060] Performance test: After testing, the gasket has a tensile strength of 20MPa and a tear resistance of 13N / mm. After continuous use for 1200 hours in a high temperature environment of 1150°C, there is no obvious performance degradation. It has good thermal insulation performance, thermal conductivity uniformity is improved by 25%, and electromagnetic shielding effectiveness reaches 15dB. It has good resistance to corrosive media such as acids and alkalis.

[0061] Example 3:

[0062] Raw materials preparation:

[0063] Ceramic fiber: a mixed fiber of aluminum silicate fiber, mullite fiber and alumina fiber (mass ratio 2:1:1), diameter 2 μm, length 20 mm, 60 parts.

[0064] High-strength organic fiber: a blend of aramid fiber and ultra-high molecular weight polyethylene fiber (mass ratio 1:1), 8 μm in diameter, 10 mm in length, 20 parts.

[0065] Nano-reinforced particles: mixed particles of nano-silicon dioxide, nano-alumina and nano-zirconium oxide (mass ratio 1:1:1), particle size 80nm, 15 parts.

[0066] High-temperature binder: 8 parts of a mixture of silica sol and aluminum phosphate solution (mass ratio 2:1).

[0067] Graphene aerogel: 5 parts, with a particle size of 1 mm after crushing.

[0068] Carbon nanotubes: 3 parts, dispersed in an ultrasonic disperser at 500 W power for 30 minutes.

[0069] Boron nitride nanosheets: 3 parts, sheet diameter 2 μm, thickness 20 nm.

[0070] Basalt fiber: 10 parts, diameter 15 μm, length 30 mm.

[0071] Production steps:

[0072] S1: Raw material pretreatment: calcining the mixed ceramic fiber in a high-temperature furnace at 500°C for 3 hours; soaking the mixed high-strength organic fiber in ethanol for 2 hours and then drying it at 80°C; stirring the mixed nano-reinforced particles in a high-speed stirrer at a speed of 1500r / min for 60 minutes; crushing the graphene aerogel; ultrasonically dispersing the carbon nanotubes; ultrasonically dispersing the boron nitride nanosheets in deionized water at a power of 400W for 25 minutes; soaking the basalt fiber in a 3% by mass silane coupling agent solution for 1 hour and then drying it at 80°C.

[0073] S2: Mixing ingredients: Add the pretreated raw materials into a high-speed mixer and mix at a speed of 1200 r / min for 40 minutes. During the mixing process, gradually add the mixed high-temperature binder and continue stirring for 20 minutes.

[0074] S3: Molding: The mixed material is placed in a mold and cold-pressed on a press at a pressure of 20 MPa to form a gasket blank, which is then placed in a drying oven and dried at 120° C. for 3 hours.

[0075] S4: High temperature sintering: Place the dried gasket blank into a high temperature furnace, heat it to 1400°C at a heating rate of 10°C / min, keep it at that temperature for 3 hours, and cool it to room temperature along with the furnace.

[0076] Performance test: After testing, the gasket has a tensile strength of 22MPa and a tear resistance of 15N / mm. After continuous use for 1500 hours in a high temperature environment of 1200°C, there is no obvious performance degradation. It has good thermal insulation performance, thermal conductivity uniformity is improved by 30%, and electromagnetic shielding effectiveness reaches 20dB. It has good resistance to corrosive media such as acids and alkalis.

[0077] Comparative Example 1:

[0078] Raw materials preparation:

[0079] Ceramic fiber: aluminum silicate fiber, diameter 3 μm, length 30 mm, 85 parts.

[0080] High temperature binder: silica sol, 15 parts.

[0081] Production steps:

[0082] S1: Raw material pretreatment: calcining the aluminum silicate fiber in a high-temperature furnace at 550° C. for 2.5 hours.

[0083] S2: Mixing ingredients: Add the pretreated aluminum silicate fiber into a high-speed mixer and stir at a speed of 800 r / min. Gradually add silica sol during the stirring process and continue stirring for 20 minutes.

[0084] S3: Molding: The mixed material is placed in a mold and cold-pressed on a press at a pressure of 10 MPa to form a gasket blank, which is then placed in a drying oven and dried at 100°C for 3 hours.

[0085] S4: High temperature sintering: Place the dried gasket green body into a high temperature furnace, heat it to 1200°C at a heating rate of 5°C / min, keep it at this temperature for 2 hours, and cool it to room temperature along with the furnace.

Claims

1. A high-strength ceramic fiber gasket, characterized in that: The gasket is made of the following raw materials in parts by weight: 60-80 parts of ceramic fiber, 10-20 parts of high-strength organic fiber, 5-15 parts of nano-reinforced particles, 5-10 parts of high-temperature adhesive, 2-5 parts of graphene aerogel, 1-3 parts of carbon nanotubes, 1-3 parts of boron nitride nanosheets, and 5-10 parts of basalt fiber.

2. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The ceramic fiber is a mixture of one or more of aluminum silicate fiber, mullite fiber, and alumina fiber, and has a diameter of 1-5 μm and a length of 10-50 mm.

3. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The high-strength organic fiber is one of aramid fiber and ultra-high molecular weight polyethylene fiber or a mixture of the two, and has a diameter of 5-15 μm and a length of 5-20 mm.

4. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The nano-reinforced particles are a mixture of one or more of nano-silicon dioxide, nano-aluminum oxide, and nano-zirconium oxide, and the particle size thereof is 50-200 nm.

5. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The high-temperature adhesive is a mixture of one or more of silica sol, aluminum phosphate solution, and water glass.

6. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The particle size of the graphene aerogel after crushing is 1-5 mm, and the carbon nanotubes are dispersed in an ultrasonic disperser at a power of 300-500 W for 20-30 minutes before use.

7. The high-strength ceramic fiber gasket according to claim 1, characterized in that: The boron nitride nanosheets have a sheet diameter of 0.5-2 μm and a thickness of 5-20 nm; the basalt fibers have a diameter of 7-15 μm and a length of 15-30 mm.

8. The method for preparing a high-strength ceramic fiber gasket according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Raw material pretreatment: calcining the ceramic fiber in a high temperature furnace at 500-600℃ for 2-3 hours; The high-strength organic fiber is soaked in an organic solvent for 1-2 hours and then dried at 80-100°C; the nano-reinforced particles are stirred in a high-speed blender at a speed of 1000-1500 r / min for 30-60 minutes; the graphene aerogel is crushed to a particle size of 1-5 mm; the carbon nanotubes are dispersed in an ultrasonic disperser at a power of 300-500 W for 20-30 minutes; the boron nitride nanosheets are ultrasonically dispersed in deionized water at an ultrasonic power of 200-400 W for 15-25 minutes; the basalt fiber is soaked in a coupling agent solution for 0.5-1 hour and then dried at 60-80°C; S2: Mixing ingredients: Add the pretreated ceramic fibers, high-strength organic fibers, nano-reinforced particles, graphene aerogel, carbon nanotubes, boron nitride nanosheets, and basalt fibers to a high-speed mixer according to the weight ratio, and mix at a speed of 800-1200 r / min for 30-40 minutes. During the mixing process, gradually add the high-temperature binder and continue stirring for 10-20 minutes to form a uniform mixture. S3: Molding: Place the mixed material into a mold and perform cold pressing on a press at a pressure of 10-20 MPa to form a gasket blank. Place the gasket blank in a drying oven and dry it at 100-120°C for 2-3 hours. S4: High temperature sintering: Place the dried gasket blank into a high temperature furnace, heat it to 1200-1400°C at a heating rate of 5-10°C / min, keep it at that temperature for 2-3 hours, and cool it to room temperature along with the furnace.

9. The method for preparing a high-strength ceramic fiber gasket according to claim 8, characterized in that: In the S1 raw material pretreatment, the organic solvent used for soaking the high-strength organic fiber is acetone or ethanol, and the coupling agent solution is a silane coupling agent solution with a mass fraction of 1-3%.

10. The method for preparing a high-strength ceramic fiber gasket according to claim 8, characterized in that: In the step S2 of mixing ingredients, the high-temperature binder is a mixed binder of silica sol and aluminum phosphate solution, and the mass ratio of the two is 2:1.